Flexor Digitorum Superficialis and Flexor Digitorum Profundus with separated sheaths (Colombia Medica, 2015)
Case description:A 25 years old man presented with a laceration on radial side of proximal phalanx of 4th finger (zone II flexor) which was due to cut with glass.Clinical findings:The sheaths of Tendons of flexor digitorum sperficialis and profundus were not the same and each tendon had a separate sheath.Treatment and outcome:The tendons were reconstructed by modified Kessler sutures, after 15 months the patient had a 30 degrees of extension lag even after physiotherapy courses.Clinical relevance:This is the first reported of such normal variation in human hand tendon anatomy.